Sports injuries prevention, treatment, and rehabilitation - Peterson, Lars; Renstrom, Per (CRC Press, Taylor & Francis Group, 2017)
This popular handbook comprehensively covers the prevention and treatment of sports injuries, and is thus essential reading for all athletes, trainers, physio-therapists and doctors. It covers all international sports and features extensive use of action photographs. For each type of injury examined, it details the symptoms, mechanism of injury, diagnosis, treatment, rehabilitation protocols, and key points--clearly stating what both non-medical and medical professionals should do in each case of injury. This easy-to-follow textbook features a glossary of key terms and protocols with rehabilitation exercises to provide readers with a solid understanding about how to effectively treat, rehabilitate, and prevent sports injuries.